Analisis Task Performance Ditinjau dari nAch dan Test of Anxiety dalam Pendidikan Vokasional - Ahmad Mujaki; Ranu Iskandar; Muhammad Irfan Nuryanta; Putri Ayu Lestari; Albert Gustafo; Ahmad Saefudin (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Need for Achievement (nAch) plays an important role in encouraging student engagement, persistence, and performance in vocational education. However, empirical studies linking nAch, task performance, and test anxiety are still limited. This study aims to analyze the relationship between nAch, test anxiety, and task performance in the context of vocational education. The study used a quantitative correlational-predictive design with linear regression analysis to examine the relationship between nAch and test anxiety on task performance. The results showed that the data were normally distributed and the regression model constructed was statistically significant (p < 0.001) with a coefficient of determination (R²) of 0.891. These findings indicate that 89.1% of the variation in task performance can be explained by nAch and test anxiety, while the remainder is influenced by other factors outside the model. Partially, nAch has a positive and significant effect on task performance, while test anxiety has a negative and significant effect. The results indicate that achievement motivation is a factor that plays an important role in improving task performance, while anxiety can be a barrier to achieving optimal performance. These findings have implications for the development of educational and training strategies that focus on enhancing achievement motivation and managing anxiety to support better student performance.